Intrauterine Exposure to Diabetic Milieu Does Not Induce Diabetes and Obesity in Male Adulthood in a Novel Rat Model. Issue 1 (January 2021) - Schütte, Till; Kedziora, Sarah M.; Haase, Nadine; Herse, Florian; Busjahn, Andreas; Birukov, Anna; Alenina, Natalia; Müller, Dominik N.; Bader, Michael; Schupp, Michael; Dechend, Ralf; Kräker, Kristin; et al.
Abstract : Several studies show an association of maternal diabetes during pregnancy with adverse offspring metabolic health. Other studies, however, suggest that this effect might be biased by obesity, which is independently associated with offspring metabolic disease and often coexistent to maternal diabetes. We performed a prospective study in a rat model to test the hypothesis that the burden of a diabetic pregnancy without obesity deteriorates metabolic health in male offspring. We generated maternal type 2 diabetes before conception that persisted during pregnancy by knockdown of the insulin receptor in small hairpin RNA–expressing transgenic rats. Male WT (wild type) offspring were followed up until adulthood and metabolically challenged by high-fat diet. Blood glucose was measured continuously via a telemetry device. Glucose and insulin tolerance tests were performed, and body composition was analyzed. Weight gain and glucose levels during adolescence and adulthood were similar in male offspring of diabetic and control pregnancies. Body weight and fat mass after high-fat diet, as well as glucose and insulin tolerance tests, were unaltered between male adult offspring of both groups. Glycemic control consisting of up to 49 000 individual glucose measures was comparable between both groups. Intrauterine exposure to maternal hyperglycemia and hyperinsulinemia without obesity had no impact on male offspring metabolic health in our model. We conclude that the intrauterine exposure itself does not represent a mechanism for fetal programming of diabetes and obesity in our model. Other maternal metabolic parameters during pregnancy, such as obesity, might impact long-term offspring metabolic health. Abstract : Supplemental Digital Content is available in the text.